Designing of a High-Quality CPR Simulation Game Clinical Scenario for Nursing Students: A Qualitative Study - Laksmi , Ida Ayu Agung; Susila, I Made Dwie Pradnya; Triana, Komang Yogi (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Cardiopulmonary resuscitation (CPR) is an important skill for nursing students. The process of learning high-quality CPR with a simulation-based learning method can be developed into a simulation game. In order to develop a CPR HQ simulation game, a clinical scenario that can be used as a guide in carrying out storyboards is needed. This research aims to formulate a simulation scenario that will serve as the basis for developing a high-quality CPR simulation game to increase nursing students' competency. This qualitative research uses a Participatory Action Research (PAR) approach by inviting 15 respondents from the prospective user population, namely Emergency Nursing Lecturers, Emergency Room Nurses, BLS Trainers, and nursing students, to carry out Focus Group Discussions. The study's results revealed clinical scenarios that were arranged based on 4 themes, including 1) suitability of the competency being tested, 2) minimum competency for 5 cycles of CPR, 3) settings in the pre-and intrahospital scope, and 4) choice of patient outcome. These components are crucial when designing simulation scenarios that support students’ cognitive processes to achieve High-Quality CPR in nursing students. Thus, the results of this research can then be used as a guide in developing the HQ-CPR game as a learning medium for nursing students.